Low-tech innovation in a high-tech environment? The case of the food industry in the Vienna metropolitan region - Michaela Trippl (European Regional Science Association (ERSA), 2010)
This paper deals with innovation activities and the pattern of knowledge linkages in the food industry located in the metropolitan region of Vienna. Drawing on 20 qualitative interviews with local companies and knowledge providers (universities and other research organisations) it is shown that in the Vienna food sector innovation has a high importance as competitive strategy. Furthermore, we demonstrate that Vienna's innovative food companies embrace a wide range of different knowledge sources. Analysing the geography of linkages to these sources, reveals that most of them are extra-local in nature. This finding has to be interpreted against the background of an ongoing reconfiguration of the regional innovation system (RIS). Vienna's RIS is in a process of transformation, becoming increasingly oriented on promoting young high-tech industries and providing only few impulses for innovation in older and more traditional sectors such as the food industry.
Keywords: 330